IMPLEMENTASI WIRAUSAHA BAKSO IKAN BANDENG DITNJAU DARI KESEJAHTERAANYA DI KELURAHAN BAURUNG, KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE PROVINSI SULAWESI BARAT - MUHAMMAD AZIZII (Jurnal Mirai Management, 2020)
Meatballs that are often circulating in the market include beef meatballs, shrimp meatballs, and chicken meatballs. Although fish meatballs have also been circulating in the community, but it is still rare for meatballs to use milk fish as the main ingredient. Park (2004). This research is planned to be carried out at the "NEW BUSINESS" Fisheries Processing and Marketers Group (POLAKSAR) located in Baurung Village, Banggae District, Majene Regency. This type of research used in this study is a qualitative study by considering the phenomena that exist. The technique used in this research is descriptive qualitative analysis and quantitative descriptive, qualitative descriptive method is used to determine the processing of milkfish meatballs and the use of milk fish as raw material for milk fish meatballs while the quantitative descriptive method is used to determine the profitability of milk fish meatball processing. Keywords : Milkfish; Income; fish meatball processor